One Health education for criticality on vaccination in teacher training - Martínez-Pena, Inés; Puig, Blanca; Uskola, Araitz (Frontiers in Public Health, 2024)
Introduction Vaccines are the basis of health of our communities since they prevent severe infectious diseases. However vaccination rates continue to decrease due to the spread of misinformation about their side effects, which enhances vaccine hesitancy and puts at risk public health. Introducing vaccines from the One Health approach can help to develop an integral understanding of their role and to apply critical ignorance as part of criticality to avoid vaccine hesitancy and raise trust in science. This paper presents a design on vaccination for secondary-education teacher training developed toward this goal. Methods The design presented in this paper draws from previous studies on critical thinking, on vaccine rejection, and the One Health approach on other health issues in Secondary Education. The focus of this design is engaging secondary-education pre-service teachers in the practice of critical ignorance and criticality to assess diverse pieces of information on vaccination from the One Health approach. Results This study discusses the design principles and the activities of an original design that aims to provide Secondary Education teachers with some tools to introduce critical ignorance and criticality for addressing misinformation on vaccines by using the One Health approach. Discussion If secondary science teachers are going to successfully confront misinformation on vaccination in their science instruction, we need to develop and test designs and approaches that prepare them for this purpose. Critical ignorance plays a central role in managing misinformation; thus, such instruction should engage future teachers in critical evaluation of information on vaccination, as well as in the application of the One Health approach to take responsible actions.